Vice and virtue - Klein, Libby (Mystery author) (Layla Virtue mystery, 2025)
"Layla is taking her new life one day at a time from the Lake Pinecrest Trailer Park she now calls home. Being alone is how she likes it. Simple. Uncomplicated. Though try telling that to the group of local ladies who are in relentless pursuit of Layla as their new BFF, determined to make her join them for coffee and donuts. Meanwhile, since her first career ended in a literal explosion, Layla's trying to eke out a living as a rock musician. It's not easy competing against garage bands who work for tacos and create their music on a computer, while all she has is an electric guitar and leather-ish pants. But Layla isn't in a position to turn down any gig. Which is why she's at an 8-year-old's birthday party, watching as Chuckles the Clown takes a bow under the balloon animals. No one expects it will be his last... Who would want to kill a clown--and why? Layla and her unshakable posse are suddenly embroiled in the seedy underbelly of the upper-class world of second wives and trust fund kids, determined to uncover what magnetic hold a pudgy, balding clown had over women who seem to have everything they could ever want. Then again, Layla knows full well that people are rarely quite what they seem--herself included..."--